Modelling the Energy Transition
XXXI, 408 p. 51 illus., 42 illus. in color.
Keywords: This open access book reconfigures Energy Transition as a global discourse from a multidisciplinary perspective. Energy Transition is not only one of the most daring technological endeavours of the present, it is also its new master narrative. Focusing on modelling both as a cultural technique and as a strategy of innovation, the chapters provided in this volume throw into relief the visions, but also the blind spots of modelling the challenges of climate change. Thus, in a rare encounter, major voices from the Sciences and the Humanities, from Energy Systems Design, Mechanical Engineering, Theory of Science, Science and Technology Studies, Literary Studies and the Arts, have gathered here to overcome the cultural divide between the technological and the societal dimensions of this global task. In doing so, they offer a new form of model criticism, pointing to the impacts of what may be termed the ‘Energy Imaginary’ on the technosocial mindsets of our time. Robert Matthias Erdbeer is a professor for German literature and literary theory at the University of Münster, Germany. His research covers literary form and modelling, experimental video games, but also the extensive contact zone of literature, philosophy of nature, and scientific thought. He has been the spokesperson of the Münster Center for Philosophy of Science. Veit Hagenmeyer holds the Chair of Energy Informatics and is the director of the Institute for Automation and Applied Informatics at Karlsruhe Institute of Technology (KIT), Germany. He is the spokesperson of the German federal national research programme ‘Energy System Design’ of the Helmholtz Association and a Director of the Energy Lab at KIT. Klaus Stierstorfer is Chair of British Studies at the University of Münster, Germany. He has published widely on literary history, literary and cultural theory, law and literature, and has an interest in literary modelling. He has been spokesperson of the Collaborative Research Centre ‘Law and Literature’ and is director of the EU CoFund Project ‘Migration, Diaspora, Citizenship’.